Analisis SWOT Bisnis Model Pada UD Mebel Jati Mandiri Di Desa Kapu Jaya, Kecamatan Palangga, Kabupaten Konawe Selatan (Perspektif Ekonomi Syariah) - Daswan, Lestari; Naswar, Naswar; Markoni, Markoni (IAIN Kendari, 2024)
This study aims to determine the SWOT Analysis of the Furniture business at UD Teak Mandiri Furniture in Kapu Jaya Village, Palangga District, South Konawe Regency and to find out how the Islamic economic perspective on the SWOT Analysis of the Furniture business at UD Teak Mandiri Furniture in Kapu Jaya Village, Palangga District, South Konawe Regency. The research method used is qualitative descriptive research with SWOT analysis (Strengths, weaknesses, opportunities, threats) using internal and external factors of the company. The results showed that the weighted value of the internal evaluation factor (IFE) matrix was 1.725 while the external matrix of the evaluation factor (EFE) was 1.11 which indicated that the development strategy that can be used by UD Mebel Jati Mandiri is the SO (Strengths-Opportunities) strategy, which combines the strengths and opportunities that exist for the company. The first SO strategy that UD Mebel Jati Mandiri can use is to continue to establish good relationships with customers, provide special discounts to existing customers who make repeat purchases, improve the skills of employees to be able to produce all forms of the latest models and maintain and continue to improve service quality. SWOT analysis on UD Mebel Jati Mandiri from the perspective of Islamic economics, aims to understand how sharia principles can be applied in business strategies to improve business competitiveness and sustainability. In this analysis what is analyzed are strengths, weaknesses, opportunities and threats. Each element of SWOT is analyzed according to Islamic principles, such as honesty, fairness, efficiency, and sustainability.